Manipulating Autophagic Processes in Autoimmune Diseases: A Special Focus on Modulating Chaperone-Mediated Autophagy, an Emerging Therapeutic Target - Wang, Fengjuan; Muller, Sylviane (Frontiers in Immunology, 2015)
Autophagy, a constitutive intracellular degradation pathway, displays essential role in the homeostasis of immune cells, antigen processing and presentation, and many other immune processes. Perturbation of autophagy has been shown to be related to several autoimmune syndromes, including systemic lupus erythematosus. Therefore modulating autophagy processes appears most promising for therapy of such autoimmune diseases. Autophagy can be said non-selective or selective; it is classified into three main forms, namely macroautophagy, microautophagy and chaperone-mediated autophagy (CMA), the former process being by far the most intensively investigated. The role of CMA remains largely underappreciated in autoimmune diseases, even though CMA has been claimed to play pivotal functions in MHC class II-mediated antigen processing and presentation. Therefore, hereby, we give a special focus on CMA as a therapeutic target in autoimmune diseases, based in particular on our most recent experimental results where a phosphopeptide modulates lupus disease by interacting with CMA regulators. We propose that specifically targeting lysosomes and lysosomal pathways, which are central in autophagy processes and seem to be altered in certain autoimmune diseases such as lupus, could be an innovative approach of efficient and personalized treatment.